Interactions Between Nutraceutical Supplements and Standard Acute Myeloid Leukemia Chemotherapeutics - Paul Spagnuolo (Frontiers Media S.A., 2015)
PURPOSE: Concomitant use of nutraceuticals with chemotherapy is very common.  Cancer patients self-medicate to relieve the side effects associated with chemotherapy, improve disease outcome and to regain control of their medical care.  However, there is limited empirical evidence on potential drug-nutraceutical interactions and their resulting effect on chemotherapy efficacy. METHOD: To investigate drug-nutraceutical interactions we created and screened a library of commonly used nutraceuticals for their modulatory effects on the activity of cytarabine and daunorubicin, two primary chemotherapeutics used to treat acute myeloid leukemia (AML).  Combination screening was performed in 3 AML cell lines (OCI-AML2, KG1a and U937) using the MTS viability assay.  Lead compounds were validated using with the Annexin V/ Propidium iodide assay and CalcuSyn drug combination software. RESULTS: We identified zinc as a nutraceutical that enhanced AML chemotherapy efficacy with combination index (CI) values of 0.649, 0.632 and 0.615 at EC 25, 50 and 75, respectively; CI values <0.9, >1.1 or between 0.9-1.1 denote statistical synergy, antagonism or additivity, respectively.  In contrast, we show that echinacea hindered AML chemotherapy efficacy by significantly reducing the ability of cytarabine to induce cell death. CONCLUSION: Given the positive and negative effects of nutraceuticals, patients undergoing chemotherapy must consult with their oncologist before consuming over-the-counter supplements.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.